1981
DOI: 10.2135/cropsci1981.0011183x002100020022x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Lamb Performance Associated with Breeding for Alkaloid Reduction in Reed Canarygrass1

Abstract: We earlier documented that indole alkaloid concentration of vegetatively propagated reed canarygrass (Phalaris arundinacea L.) clones was inversely associated with average daily gains of lambs and steers. Our objectives were to determine whether alkaloid concentration and type in two commercially available cultivars (‘Rise’ and ‘Vantage’) and in a low‐alkaloid, tryptamine‐carboline‐free strain (MN‐76) were associated with performance and health of grazing lambs. These seed sources of reed canarygrass were each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Total indole alkaloid concentration (gramine, tryptamines and carbolines) was inversely correlated with weight gains in lambs and steers (Marten et al 1976). Marten et al (1981) indicated that a total alkaloid concentration greater than 2.0 mg/g dry weight of forage reduces animal gains. Similarly, palatability was correlated with total alkaloid concentration (Simons and Marten 1971).…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 95%
See 1 more Smart Citation
“…Total indole alkaloid concentration (gramine, tryptamines and carbolines) was inversely correlated with weight gains in lambs and steers (Marten et al 1976). Marten et al (1981) indicated that a total alkaloid concentration greater than 2.0 mg/g dry weight of forage reduces animal gains. Similarly, palatability was correlated with total alkaloid concentration (Simons and Marten 1971).…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 95%
“…They reduce palatability of the grass, and thus serve as animal deterrants to prevent overgrazing (Marten et al 1976). The tryptamine and carboline alkaloids create digestive disorders resulting in a greater incidence of diarrhea in sheep compared to either the hordenine or gramine alkaloids (Marten et al 1981). Hordenine and gramine alkaloids simply reduce average daily gains.…”
Section: Phalaris Species (Reed Canarygrass)mentioning
confidence: 99%
“…The levels of gramine detected in these samples should not affect ruminant performance as Marten et al (1981) determined the values of indole alkaloids below 2 ^g g ' DM had no effect on the ruminant animal.…”
mentioning
confidence: 87%
“…Animals had more diarrhea when grazing high-alkaloid plants and when grazing tryptamine-carboline-containing as compared with gramine-containing plants. MARTEN et al (1981) studied whether alkaloid concentration and type were associated with performance and health of grazing lambs, using cultivars with different alkaloid types and concentration levels. The strain MN-76 and the cultivars Vantage and Rise had mean alkaloid concentrations of 0.105,0.265 and 0.300 YO of the dry weight, respectively.…”
Section: A Effect On Fodder Qualitymentioning
confidence: 99%